Intergenerational inequality aversion, growth and the role of damages: Occam's rule for the global carbon tax - Van der Ploeg, R; Rezai, A (University of Oxford, 2014)
We derive a simple rule for a nearly optimal carbon tax that can be implemented and tested in a decentralized market economy. Our simple rule depends on the effect of the pure rate of time preference, growth and intergenerational inequality aversion and basic parameters of the carbon cycle, but also on any adverse effects of global warming on economic growth and mean reversion in climate damages. The performance of the simple rule is excellent and yields only tiny welfare losses compared with the true welfare optimum under a wide range of perturbations including some extreme runs designed to severely road-test the rule. Our IAM allows for scarce fossil fuel and endogenous energy transitions and generates cumulative carbon emissions and stranded assets which are also well predicted by our rule.